Performance of Surgical Stress Index during Sevoflurane-Fentanyl and Isoflurane-Fentanyl Anesthesia - S. Mustola; T. Parkkari; K. Uutela; M. Huiku; M. Kymäläinen; J. Toivonen (Anesthesiology Research and Practice)
The performance of recently introduced Surgical Stress Index (SSI), based on heart rate and photoplethysmography, was estimated during sevoflurane-fentanyl and isoflurane-fentanyl anesthesia during surgical procedures. Forty ASA I–III patients were enrolled. Anesthesia was induced with fentanyl 2 μg kg−1 and thiopentone 3–5 mg kg−1. Tracheal intubation was performed 5 minutes after fentanyl bolus. Patients were randomly allocated to receive sevoflurane (n=20) or isoflurane (n=20) in 30% oxygen/air. State entropy was kept at 40–60, target being 50. During surgery, fentanyl boluses 1.5 μg kg−1 were given at 30–40-minute intervals. SSI increased significantly after intubation. During surgery, the decrease of SSI after fentanyl boluses was similar in sevoflurane and isoflurane groups but SSI values were higher in sevoflurane than in isoflurane group. Tracheal intubation, skin incision, and surgical stimuli increased SSI from baseline, indicating that nociceptive stimuli increase SSI. Fentanyl boluses during surgery decreased SSI, indicating that increasing analgesia decreases SSI.